KAJIAN PENERAPAN PMMT PRODUK OLAHAN HASILPERIKANAN TRADISIONAL DALAM RANGKA PENINGKATAN PENGAMAN PANGAN MENGACU PADA HACCP - Sudibjono Sudibjono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The application of PMMT, based on the concept ofHACCP in traditional processing unit of home-industry fisheries products are an obligation for food safety demand. It aims to give better quality and safety guarantee of the product processed as written in the Minister of Agriculture decree no.41/Kpts/lk. 210/2/1998. The survey is aimed to study how far the traditional processing unit has applied PMMT based on the conception ofHACCP, in its effort to give the best quality product. The character of survey is descriptive explorative using observation and interview methods. The Interview is based on the check list/ assessment sheet, question list for the traditional processor, as verification of the implementation of PMMT. It is conducted by directly observe the practice in processing unit, and test product supported by the standart of TPC bacteria allowed, before and after guidance is given. The result shows that: I. The traditional processing unit in the form of home industry is not suitable for high quality fisheries product. 2. The number ofTPC bacterian after guidance is less than before qui dance and it is included in SNJ (Standard National Indonesia). 3 The traditional processor received, is used in the effort to give the best quality product